ANALISIS NILAI TAMBAH BUNGA POTONG KRISAN PADA NINGSIH FLORIST DI KOTA TOMOHON - Merry Shenly Tololiu; Paulus A. Pangemanan; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2016)
The objective of this research is to analyze the value added of chrysanthemum flowers on Ningsih Florist. The research was conducted for 4 months in Kakaskasen II, Tomohon City. The data were obtained by direct interviews with business owners and then analyzed by descriptive quantitatively. The research results showed that acceptance ningsih florist business where the average monthly spending Â± 5.148 stalk of chrysanthemum flowers with the acceptance of all the flower arrangements, namely IDR. 66,040,000.00. Enterprises chrysanthemum flower arrangements by Ningsih Florist as a whole can benefit and deserves to be developed. It is based on the analysis of the value added that gross value added amounted to IDR. 16,729,984.20, net value added IDR. 16,683,734.20, value added every feedstock IDR. 3249.80 / stalk. The calculated value added that each item is flower corsage flower arrangement has the value added IDR. 4,424 / item, bouquets IDR. 212 249 / item, flower table IDR. 914 / item, floral wreaths IDR. 8,615 / item, and flower board IDR. 115 140 / item.